Composite conductive ink, transparent conductive film and preparation method thereof

By adding nano-copper wire and aqueous additives to the nano-silver wire conductive ink, a nano-silver wire-nano-copper wire composite conductive film is solved, and the problem of unstable aging performance of nano-silver wire transparent conductive film under long-term light is significantly improved. It has oxidation resistance and stability, and maintains electrical conductivity and light transmission properties.

CN114171239BActive Publication Date: 2024-12-13SHENZHEN HUAKE COMM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111440998.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-30
Publication Date
2024-12-13
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

The nano-silver transparent conductive film has unstable aging performance under long-term light illumination and is prone to oxidation, resulting in a decrease in conductivity, limiting its development in the electronic field.

Method used

Add nano-copper wire to the nano-silver wire conductive ink, use the easy oxidation properties of copper to protect the nano-silver wire, combine aqueous additives and alcohol dispersants to form nano-silver wire-nano-copper wire composite conductive ink, which is heat-cured or photo-cured Form a composite conductive layer and a protective layer to improve oxidation resistance and stability.

Benefits of technology

The antioxidant performance and stability of the nano-silver wire conductive film is significantly improved, the aging performance is extended, the light transmittance and electrical conductivity of the conductive film is maintained, and the rate of change in performance after aging is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114171239B_ABST
    Figure CN114171239B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of liquid crystal technology, and specifically relates to a composite conductive ink, a transparent conductive film and a preparation method thereof. A composite conductive ink, comprising: nano silver wire ink and nano copper wire ink, wherein the nano silver wire ink accounts for 85-95% by volume, and the nano copper wire ink accounts for 5-15% by volume. The present invention adds a small amount of nano copper wire to the nano silver wire conductive ink, and utilizes the property that copper is more active and easily oxidized than silver, thereby well protecting the nano silver wire from oxidation, improving the oxidation resistance of the nano silver wire conductive film, and solving the problem of increased resistance of the nano silver wire conductive film after long-term light aging; and the selected nano copper wire has excellent optical and electrical properties, and will not affect the light transmittance and conductivity of the nano silver wire conductive film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid crystal, and in particular relates to a composite conductive ink, a transparent conductive film and a preparation method thereof. Background Art

[0002] Transparent conductive film is a film that can conduct electricity and has high transmittance in the visible light range. The most important application at present is ITO conductive film, but it has the problems of high price, poor flexibility, high energy consumption and high resistance. In addition to the excellent conductivity of silver, silver nanowires also have excellent light transmittance and flex resistance due to the size effect at the nano level. Therefore, it is regarded as the most likely material to replace the traditional ITO transparent electrode, which provides the possibility of realizing flexible and bendable LED displays, touch screens, etc. In addition, due to the large aspect ratio effect of silver nanowires, it also has outstanding advantages in the application of conductive adhesives, thermal conductive adhesives, etc. However, the transparent conductive film of nano silver wires has problems such as unstable aging performance and large haze, which limits its development in the field of electronics.

[0003] At present, most of the nano silver wire transparent conductive films mainly include a substrate layer, a nano silver wire conductive layer and an optical adhesive layer. The method of improving the anti-oxidation performance of the nano silver wire conductive film in the prior art is mainly to add an antioxidant to the optical adhesive layer. However, the anti-oxidation nano silver wire transparent conductive film prepared by this method is unstable under long-term irradiation of UV, xenon lamp, etc., and the nano silver wire is easily oxidized and fails. Therefore, it is very important to provide a composite conductive ink and a transparent conductive film. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a composite conductive ink, a transparent conductive film and a preparation method thereof, and the oxidation resistance and stability of the prepared nano silver wire conductive film are greatly improved.

[0005] In a first aspect, the present invention provides a composite conductive ink, comprising: nano silver wire ink and nano copper wire ink, wherein the nano silver wire ink accounts for 85-95% by volume, and the nano copper wire ink accounts for 5-15% by volume;

[0006] Preferably, the nano silver wire ink accounts for 85-90% by volume, and the nano copper wire ink accounts for 10-15% by volume.

[0007] Furthermore, the nano silver wire ink comprises:

[0008] Nano silver wire 0.5-3%;

[0009] Dispersant 0.02-0.05%;

[0010] Isopropyl alcohol 10-20%;

[0011] Photoinitiator 0.05-0.5%;

[0012] Leveling agent 0.05-0.5%; and,

[0013] Water balance.

[0014] More preferably, the nano silver wire ink comprises:

[0015] Nano silver wire 2%;

[0016] Dispersant 0.04%;

[0017] Isopropyl alcohol 18%;

[0018] Photoinitiator 0.4%;

[0019] Leveling agent 0.4%;

[0020] Water balance.

[0021] Furthermore, the nano copper wire ink comprises:

[0022] Nano copper wire 1-3%;

[0023] Dispersant 0.02-0.05%;

[0024] Isopropyl alcohol 10-20%; and,

[0025] Water balance.

[0026] More preferably, the nano copper wire ink comprises:

[0027] Nano copper wire 2%;

[0028] Dispersant 0.04%;

[0029] Isopropyl alcohol 18%; and,

[0030] Water balance.

[0031] Furthermore, the diameter of the silver nanowire is 20-60 nm, and the length is 10-50 μm; more preferably, the diameter of the silver nanowire is 30 nm, and the length is 25 μm.

[0032] Furthermore, the diameter of the nano copper wire is 20-60 nm, and the length is 10-50 μm; more preferably, the diameter of the nano copper wire is 25 nm, and the length is 15 μm.

[0033] Furthermore, the dispersant is at least one of polyethylene glycol, polyvinyl alcohol, ethanol, isopropanol, and n-butanol.

[0034] Furthermore, the photoinitiator is at least one of MBE, TPO, ITX, 184, 907, 819, and CTX.

[0035] Furthermore, the leveling agent is at least one of propylene glycol methyl ether, diacetone alcohol, cyclohexanol and propylene glycol.

[0036] In a second aspect, the present invention further provides a transparent conductive film, which is formed by coating the composite conductive ink as described above onto the surface of a transparent substrate and curing it.

[0037] In a third aspect, the present invention further provides a method for preparing the transparent conductive film as described above, comprising the following steps:

[0038] (1) Plasma treatment of transparent substrates;

[0039] (2) coating the composite conductive ink on the transparent substrate and forming a nanosilver wire-nanocopper wire composite conductive layer after curing;

[0040] (3) applying the optical adhesive coating liquid onto the surface of the nano silver wire-nano copper wire composite conductive layer, and forming a protective layer after curing to obtain a nano silver wire transparent conductive film.

[0041] Specifically, the transparent substrate includes polyethylene resin, polyester resin, polycarbonate resin, acrylic resin, cellulose resin, or the like.

[0042] Specifically, the optical adhesive layer includes thermoplastic resins such as polyester resin, cellulose resin, vinyl resin, acrylic resin, polycarbonate resin, etc., photocurable resin, and thermosetting resin.

[0043] Specifically, in step (2), the composite conductive layer is cured by thermal curing at a temperature of 70-110° C.; in step (3), the protective layer is cured by thermal curing or photocuring at a temperature of 60-100° C.

[0044] Specifically, the thickness of the transparent substrate is 6-200 μm, the thickness of the composite conductive layer is 15-250 nm, and the thickness of the protective layer is 20-150 nm; more preferably, the thickness of the composite conductive layer is 80 nm, and the thickness of the protective layer is 60 nm.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The present invention adds a small amount of nano copper wire to the nano silver wire conductive ink, and utilizes the property that copper is more active than silver and is easily oxidized, thereby well protecting the nano silver wire from oxidation, improving the anti-oxidation property of the nano silver wire conductive film, and solving the problem that the resistance of the nano silver wire conductive film increases after long-term light aging; and the selected nano copper wire has excellent optical and electrical properties, and will not affect the light transmittance and conductivity of the nano silver wire conductive film; the composite conductive ink of the present invention is mainly water-based additives, green and environmentally friendly, and a small amount of alcohol is added as a dispersant so that the nano silver wire and nano copper wire in the conductive ink are evenly dispersed, and the dispersion stability is good; propylene glycol is added as a leveling agent so that the fluidity and leveling property of the composite conductive ink are improved, and the nano silver wire-nano copper wire composite conductive ink can be evenly spread on the surface of the transparent substrate to form a film. The nano silver wire-nano copper wire composite conductive film prepared by the composite conductive ink with high anti-oxidation property of the present invention has good anti-oxidation property and significantly improved stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a SEM image of silver nanowires, the diameter of which is 30 nm;

[0048] Figure 2 This is a SEM image of a nano-copper wire, the diameter of the nano-copper wire is 25nm;

[0049] Figure 3 is a SEM image of the silver nanowire transparent conductive film prepared in Example 3 after aging for 200 hours;

[0050] Figure 4 This is a SEM image of the nano silver wire transparent conductive film prepared in Comparative Example 1 after aging for 200 hours. DETAILED DESCRIPTION

[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0052] Example 1

[0053] (1) preparing a nano silver wire ink: 2% of nano silver wire, 0.04% of polyethylene glycol, 18% of isopropyl alcohol, 0.4% of photoinitiator MBE, 0.4% of propylene glycol methyl ether, and the balance of water were mixed evenly to obtain a nano silver wire ink with a concentration of 2 wt %, wherein the average diameter of the nano silver wire was 30 nm and the average length was 25 μm;

[0054] (2) preparing nano copper wire ink: 2% nano copper wire, 0.04% polyethylene glycol, 18% isopropyl alcohol, and the balance water were mixed evenly to obtain a nano copper wire ink with a concentration of 2 wt %, wherein the nano copper wire had an average diameter of 25 nm and an average length of 15 μm;

[0055] (3) preparing a composite conductive ink: mixing 9 L of the silver nanowire ink prepared in step (1) and 1 L of the copper nanowire ink prepared in step (2), and stirring for 1 h to form a silver nanowire-copper nanowire composite conductive ink;

[0056] (4) Preparation of a transparent conductive film: Using PET with a surface corona treatment as a transparent substrate (visible light transmittance of 91.8%), a slit coater was used to apply the nanosilver wire-nanocopper wire composite conductive ink prepared in step (3) onto the surface of the PET, and the mixture was dried at 100° C. to form a nanosilver wire-nanocopper wire composite conductive layer with a thickness of 80 nm;

[0057] Applying protective layer coating liquid: on the surface of the prepared PET / nano silver wire-nano copper wire composite conductive layer, a layer of polyurethane optical adhesive layer coating liquid is applied by a slit coater, and dried at 85° C. to form a protective layer with a thickness of 60 nm;

[0058] A transparent conductive film is obtained.

[0059] Example 2

[0060] (1) preparing a nano silver wire ink: mixing 1% nano silver wire, 0.03% polyvinyl alcohol, 15% isopropyl alcohol, 0.2% photoinitiator TPO, 0.2% diacetone alcohol, and the balance water to obtain a nano silver wire ink with a concentration of 1 wt %, wherein the average diameter of the nano silver wire is 30 nm and the average length is 25 μm;

[0061] (2) preparing nano copper wire ink: 1.5% nano copper wire, 0.03% polyvinyl alcohol, 15% isopropyl alcohol, and the balance water were mixed evenly to obtain a nano copper wire ink with a concentration of 1.5 wt %, wherein the average diameter of the nano copper wire was 25 nm and the average length was 15 μm;

[0062] (3) preparing a composite conductive ink: mixing 8.5 L of the silver nanowire ink prepared in step (1) and 1.5 L of the copper nanowire ink prepared in step (2), and stirring for 1 h to form a silver nanowire-copper nanowire composite conductive ink;

[0063] (4) Preparation of a transparent conductive film: Using PET with a surface corona treatment as a transparent substrate (visible light transmittance of 91.8%), a slit coater was used to apply the nanosilver wire-nanocopper wire composite conductive ink prepared in step (3) onto the surface of the PET, and the coating was dried at 80° C. to form a nanosilver wire-nanocopper wire composite conductive layer with a thickness of 100 nm;

[0064] Applying protective layer coating liquid: on the surface of the prepared PET / nanosilver wire-nanocopper wire composite conductive layer, a layer of polythiophene optical adhesive layer coating liquid is applied by a slit coater, and dried at 100° C. to form a protective layer with a thickness of 50 nm;

[0065] A transparent conductive film is obtained.

[0066] Example 3

[0067] (1) preparing a nano silver wire ink: 0.5% of nano silver wires, 0.02% of ethanol, 10% of isopropyl alcohol, 0.05% of photoinitiator ITX, 0.05% of cyclohexanol, and the balance of water were mixed uniformly to obtain a nano silver wire ink with a concentration of 0.5 wt %, wherein the average diameter of the nano silver wires was 30 nm and the average length was 25 μm;

[0068] (2) preparing nano copper wire ink: 1% nano copper wire, 0.02% ethanol, 10% isopropanol, and the balance water were mixed evenly to obtain a nano copper wire ink with a concentration of 1 wt%, wherein the nano copper wire had an average diameter of 25 nm and an average length of 15 μm;

[0069] (3) preparing a composite conductive ink: mixing 8 L of the silver nanowire ink prepared in step (1) and 2 L of the copper nanowire ink prepared in step (2), and stirring for 1 h to form a silver nanowire-copper nanowire composite conductive ink;

[0070] (4) Preparation of a transparent conductive film: Using PI with a surface corona treatment as a transparent substrate (visible light transmittance of 89.7%), a slit coater was used to apply the nanosilver wire-nanocopper wire composite conductive ink prepared in step (3) onto the PI surface, and the slit coater was used to dry the PI surface at 70° C. to form a nanosilver wire-nanocopper wire composite conductive layer with a thickness of 150 nm;

[0071] Applying protective layer coating liquid: on the surface of the prepared PI / nanosilver wire-nanocopper wire composite conductive layer, a layer of polyacrylic resin optical adhesive layer coating liquid is applied by a slit coater, and dried at 90° C. to form a protective layer with a thickness of 80 nm;

[0072] A transparent conductive film is obtained.

[0073] Example 4

[0074] (1) preparing nano silver wire ink: 3% nano silver wire, 0.05% n-butanol, 20% isopropanol, 0.5% photoinitiator 819, 0.5% propylene glycol, and the balance water were mixed uniformly to obtain a nano silver wire ink with a concentration of 3 wt %, wherein the average diameter of the nano silver wire was 30 nm and the average length was 25 μm;

[0075] (2) preparing nano copper wire ink: 3% nano copper wire, 0.05% n-butanol, 20% isopropanol, and the balance water were mixed evenly to obtain a nano copper wire ink with a concentration of 3 wt %, wherein the nano copper wire had an average diameter of 25 nm and an average length of 15 μm;

[0076] (3) preparing a composite conductive ink: mixing 9.5 L of the silver nanowire ink prepared in step (1) and 0.5 L of the copper nanowire ink prepared in step (2), and stirring for 1 h to form a silver nanowire-copper nanowire composite conductive ink;

[0077] (4) Preparation of a transparent conductive film: Using PI with a surface corona treatment as a transparent substrate (visible light transmittance of 89.7%), a slit coater was used to apply the nanosilver wire-nanocopper wire composite conductive ink prepared in step (3) above to the PI surface, and dried at 110° C. to form a nanosilver wire-nanocopper wire composite conductive layer with a thickness of 200 nm;

[0078] Applying protective layer coating liquid: on the surface of the prepared PI / nano-silver wire-nano-copper wire composite conductive layer, a layer of polyvinyl alcohol optical adhesive layer coating liquid is applied by a slit coater, and dried at 60° C. to form a protective layer with a thickness of 100 nm;

[0079] A transparent conductive film is obtained.

[0080] Example 5

[0081] (1) preparing nano silver wire ink: 1.5% nano silver wire, 0.03% polyvinyl alcohol, 16% isopropyl alcohol, 0.2% photoinitiator 907, 0.2% cyclohexanol, and the balance water were mixed uniformly to obtain a nano silver wire ink with a concentration of 1.5 wt %, wherein the average diameter of the nano silver wire was 30 nm and the average length was 25 μm;

[0082] (2) preparing nano copper wire ink: 1.8% nano copper wire, 0.03% polyvinyl alcohol, 16% isopropyl alcohol, and the balance water were mixed evenly to obtain a nano copper wire ink with a concentration of 1.8wt%, wherein the average diameter of the nano copper wire was 25nm and the average length was 15μm;

[0083] (3) preparing a composite conductive ink: mixing 8.8 L of the silver nanowire ink prepared in step (1) and 1.2 L of the copper nanowire ink prepared in step (2), and stirring for 1 h to form a silver nanowire-copper nanowire composite conductive ink;

[0084] (4) Preparation of a transparent conductive film: Using PE with a surface corona treatment as a transparent substrate (visible light transmittance of 90.2%), a slit coater was used to apply the nanosilver wire-nanocopper wire composite conductive ink prepared in step (3) above to the PE surface, and dried at 85° C. to form a nanosilver wire-nanocopper wire composite conductive layer with a thickness of 60 nm;

[0085] Applying protective layer coating liquid: on the surface of the prepared PE / nano silver wire-nano copper wire composite conductive layer, a layer of epoxy resin optical adhesive layer coating liquid is applied by a slit coater, and dried at 70° C. to form a protective layer with a thickness of 30 nm;

[0086] A transparent conductive film is obtained.

[0087] Example 6

[0088] (1) preparing nano silver wire ink: 2.5% nano silver wire, 0.05% isopropyl alcohol, 18% isopropyl alcohol, 0.4% photoinitiator 184, 0.4% propylene glycol, and the balance water were mixed uniformly to obtain a nano silver wire ink with a concentration of 2.5 wt %, wherein the average diameter of the nano silver wire was 30 nm and the average length was 25 μm;

[0089] (2) preparing nano copper wire ink: 2.5% nano copper wire, 0.05% isopropyl alcohol, 18% isopropyl alcohol, and the balance water were mixed evenly to obtain a nano copper wire ink with a concentration of 2.5wt%, wherein the average diameter of the nano copper wire was 25nm and the average length was 15μm;

[0090] (3) preparing a composite conductive ink: mixing 9.2 L of the silver nanowire ink prepared in step (1) and 0.8 L of the copper nanowire ink prepared in step (2), and stirring for 1 h to form a silver nanowire-copper nanowire composite conductive ink;

[0091] (4) Preparation of a transparent conductive film: Using PE with a surface corona treatment as a transparent substrate (visible light transmittance of 90.2%), a slit coater was used to apply the nanosilver wire-nanocopper wire composite conductive ink prepared in step (3) above to the PE surface, and the slit coater was used to dry the PE surface at 95° C. to form a nanosilver wire-nanocopper wire composite conductive layer with a thickness of 250 nm;

[0092] Applying protective layer coating liquid: on the surface of the prepared PE / nano silver wire-nano copper wire composite conductive layer, a layer of methyl cellulose optical adhesive coating liquid is applied by a slit coater, and dried at 80° C. to form a protective layer with a thickness of 150 nm;

[0093] A transparent conductive film is obtained.

[0094] Comparative Example 1

[0095] (1) preparing a nano silver wire ink: 0.5% of nano silver wires, 0.02% of ethanol, 10% of isopropyl alcohol, 0.05% of photoinitiator ITX, 0.05% of cyclohexanol, and the balance of water were mixed uniformly to obtain a nano silver wire ink with a concentration of 0.5 wt %, wherein the average diameter of the nano silver wires was 30 nm and the average length was 25 μm;

[0096] (2) Preparation of a transparent conductive film: Using PET with a corona-treated surface as a transparent substrate (visible light transmittance of 91.8%), a slit coater was used to apply the silver nanowire conductive ink prepared in step (1) onto the surface of the PET, and the film was dried at 70° C. to form a silver nanowire conductive layer with a thickness of 150 nm;

[0097] Applying protective layer coating liquid: on the surface of the prepared PET / nanosilver wire conductive layer, a layer of polyurethane optical adhesive layer coating liquid is applied by a slit coater, and dried at 90° C. to form a protective layer with a thickness of 80 nm;

[0098] A transparent conductive film is obtained.

[0099] Comparative Example 2

[0100] (1) preparing nano silver wire ink: 3% nano silver wire, 0.05% n-butanol, 20% isopropanol, 0.5% photoinitiator 819, 0.5% propylene glycol, and the balance water were mixed uniformly to obtain a nano silver wire ink with a concentration of 3 wt %, wherein the average diameter of the nano silver wire was 30 nm and the average length was 25 μm;

[0101] (2) Preparation of a transparent conductive film: Using PET with a corona-treated surface as a transparent substrate (visible light transmittance of 91.8%), a slit coater was used to apply the silver nanowire conductive ink prepared in step (1) onto the surface of the PET, and the coating was dried at 110° C. to form a silver nanowire conductive layer with a thickness of 200 nm;

[0102] Applying protective layer coating liquid: on the surface of the prepared PET / nanosilver wire conductive layer, a layer of polyvinyl alcohol optical adhesive layer coating liquid is applied by a slit coater, and dried at 60° C. to form a protective layer with a thickness of 100 nm;

[0103] A transparent conductive film is obtained.

[0104] The contents of each component and related process parameters of Examples 1-6 and Comparative Examples 1-2 are shown in Table 1.

[0105] Table 1

[0106]

[0107] The sheet resistance, transmittance, haze, yellowness value and performance index after aging of the transparent conductive films prepared in the above embodiments and comparative examples were tested. The test results are shown in Table 2.

[0108] The test methods for sheet resistance, transmittance, haze, yellowness and aging performance of transparent conductive films are as follows:

[0109] Sheet resistance (R): Use a four-point probe sheet resistance tester to test the sheet resistance of the transparent conductive film. At least six points should be randomly collected for testing and the average value should be calculated. Before testing, the transparent conductive film should be placed flat, the temperature should be 23±5℃, and the relative humidity should be (50±10)%RH. ;

[0110] Transmittance (T) and haze (H): Use a transmittance / haze meter, refer to the standard GB / T 2041-2008 Determination of transmittance and haze of transparent plastics, temperature 23±5℃, relative humidity: (50±10)%RH.

[0111] Yellowness (b * ): Use a colorimeter, refer to standard GB / T 2409-1980 Plastic Yellowness Index Test Method, temperature 23±5℃, relative humidity: (50±10)%RH.

[0112] Aging performance test: humidity 95% RH, temperature 60℃, time 240h, refer to the standard environment of plastic sample state adjustment and test in GB / T 2918-1998;

[0113] Resistance change (ΔR) = (R 老化后 -R 老化前 ) / R 老化前 ×100%;

[0114] Transmittance change (ΔT) = (T 老化后 -T 老化前 ) / T 老化前 ×100%;

[0115] Haze change (ΔH) = (H 老化后 -H 老化前 ) / H 老化前 ×100%;

[0116] Yellowness change (Δb * )=(b* 老化后 -b * 老化前 ) / b * 老化前 ×100%.

[0117] Table 2

[0118]

[0119]

[0120] It can be seen from the data in Table 1 that the nanosilver wire-nanocopper wire composite transparent conductive film formed after adding nanocopper wire in Examples 1-6 and the nanosilver wire transparent conductive film formed in Comparative Examples 1-2 without adding nanocopper wire have similar initial properties such as initial square resistance, transmittance, haze, and yellowness test results, indicating that the addition of nanocopper wire does not affect the optical and electrical properties of the nanosilver wire conductive film.

[0121] However, after aging for 200h, the performance of the two types of nano silver wire conductor films showed great differences: the performance of the nano silver wire-nano copper wire composite transparent conductive film formed by adding nano copper wire in Example 1-6 changed slightly, the change rate of square resistance was 1.54-5.24%, the change rate of visible light transmittance was (-0.66)-(-0.89)%, the change rate of haze was 0.47-5.63%, and the change rate of yellowness was (-1.39)-(-3.78)%; while the performance of the nano silver wire transparent conductive film formed by comparative example 1-2 without adding nano copper wire changed significantly, the change rate of square resistance was 23.55-39.92%, the change rate of visible light transmittance was (-1.31)-(-1.75)%, the change rate of haze was 35.10-38.21%, and the change rate of yellowness was 9.24-15.86%, and the performance was significantly reduced.

[0122] And, by Figure 3 The SEM image shows that the nanosilver wire transparent conductive film without nanocopper wire in comparative example 1 is oxidized and broken after aging for 200h, while Figure 4 SEM image shows that the nanosilver wire-nanocopper wire composite transparent conductive film formed after adding nanocopper wire in Example 3 has a good shape after aging for 200 hours. It can be seen that the nanosilver wire conductive film with added nanocopper wire has excellent anti-oxidation performance, and even after aging for 200 hours, the optical and electrical properties remain in good condition.

[0123] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A composite conductive ink, characterized in that: include: Nano silver wire ink and nano copper wire ink, wherein the nano silver wire ink accounts for 85-95% by volume, and the nano copper wire ink accounts for 5-15% by volume; The nano silver wire ink comprises: 0.5-3% nano silver wire, 0.02-0.05% dispersant, 10-20% isopropyl alcohol, 0.05-0.5% photoinitiator, 0.05-0.5% leveling agent, and the balance of water; The nano copper wire ink comprises: 1-3% nano copper wire, 0.02-0.05% dispersant, 10-20% isopropyl alcohol, and the balance water.

2. The composite conductive ink according to claim 1, characterized in that: The diameter of the nano silver wire is 20-60 nm, and the length is 10-50 μm.

3. The composite conductive ink according to claim 1, characterized in that: The diameter of the nano copper wire is 20-60 nm, and the length is 10-50 μm.

4. The composite conductive ink according to claim 1, characterized in that: The dispersant is at least one of polyethylene glycol, polyvinyl alcohol, ethanol, isopropanol and n-butanol.

5. The composite conductive ink according to claim 1, characterized in that: The photoinitiator is at least one of MBE, TPO, ITX, 184, 907, 819, and CTX.

6. The composite conductive ink according to claim 1, characterized in that: The leveling agent is at least one of propylene glycol methyl ether, diacetone alcohol, cyclohexanol and propylene glycol.

7. A transparent conductive film, characterized in that: The composite conductive ink according to any one of claims 1 to 6 is coated on the surface of a transparent substrate and cured to form the composite conductive ink.

8. A method for preparing the transparent conductive film as claimed in claim 7, characterized in that: The following steps are involved: (1) Plasma treatment of transparent substrates; (2) coating the composite conductive ink on the transparent substrate and forming a nanosilver wire-nanocopper wire composite conductive layer after curing; (3) applying an optical adhesive coating liquid onto the surface of the nano-silver wire-nano-copper wire composite conductive layer, and forming a protective layer after curing to obtain a nano-silver wire transparent conductive film.